Meta Analisis: High Order Thinking Skills - Zulfah Zulfah; Astuti Astuti; Dicky Ezaldi; Eri Hakim Firmansyah; Hafizah Risali; Lina Suryani; Melani Felantini Putri; Rian Aristi; Yelvi Rahmadani (Journal on Education, 2022)
High Order Thinking Skill or Higher Order Thinking Ability is one of the abilities that is the goal in learning mathematics. Students are said to have High Order Thinking Skills (HOTS) if they fulfill three aspects, namely analyzing, evaluating, and creating. It is necessary to get used to it from an early age, through various models, strategies, or learning approaches. There are several studies that have tested the effect of learning models, approaches, or learning strategies including through the application of Problem Based Learning, Web-Based Project Based Learning, scientific approaches and Problem Solving. The purpose of this study was to analyze the impact of learning models and approaches on HOTS. This study uses a meta-analysis method with a sample of 5 articles from national journals and in the form of a coding category instrument. This study proves that the effect of methods, models and approaches on HOTS, HOTS is more influenced by the Problem Solving learning method.